2017
DOI: 10.7326/m16-1895
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Abnormalities Among Normal-Weight Persons From Five Racial/Ethnic Groups in the United States

Abstract: Background The relationship between body weight and cardiometabolic disease may vary substantially by race/ethnicity. Objective To determine the prevalence and correlates of the phenotype of metabolic abnormality but normal weight (MAN) for 5 racial/ethnic groups. Design Cross-sectional analysis. Setting 2 community-based cohorts. Participants 2622 white, 803 Chinese American, 1893 African American, and 1496 Hispanic persons from MESA (Multi-Ethnic Study of Atherosclerosis) and 803 South Asian particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 35 publications
(37 reference statements)
1
65
0
2
Order By: Relevance
“…Obesity was defined as BMI 18.5-23.9 kg/m 2 and metabolic abnormality referenced at least two abnormal traits among the factors of TG, HDL-C, BP and FPG. Using the same definition of metabolic risk, the Multi-Ethnic Study of Atherosclerosis showed high variability in the prevalence of metabolically unhealthy with normal-weight individuals based on ethnicity: The prevalence was 21.0% in Whites, 32.2% in Chinese Americans, 31.1% in African Americans, 38.5% in Hispanics, and 43.6% in South Asians [21]. The prevalence among Chinese was highly consistent between our findings in mainland China and the findings in America.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was defined as BMI 18.5-23.9 kg/m 2 and metabolic abnormality referenced at least two abnormal traits among the factors of TG, HDL-C, BP and FPG. Using the same definition of metabolic risk, the Multi-Ethnic Study of Atherosclerosis showed high variability in the prevalence of metabolically unhealthy with normal-weight individuals based on ethnicity: The prevalence was 21.0% in Whites, 32.2% in Chinese Americans, 31.1% in African Americans, 38.5% in Hispanics, and 43.6% in South Asians [21]. The prevalence among Chinese was highly consistent between our findings in mainland China and the findings in America.…”
Section: Discussionmentioning
confidence: 99%
“…The BMI categories for overweight and obesity used by the WHO are based on data primarily from populations of European origin living in high‐income countries. A WHO expert consultation concluded that substantial proportions of Asians with a high risk of type 2 diabetes and cardiovascular disease are classified as having a “normal” weight, suggesting that using the same categories for all racial/ethnic groups may result in overlooking a large proportion of at‐risk individuals in some populations …”
Section: Defining Excess Body Weightmentioning
confidence: 99%
“…A WHO expert consultation concluded that substantial proportions of Asians with a high risk of type 2 diabetes and cardiovascular disease are classified as having a "normal" weight, 20 suggesting that using the same categories for all racial/ethnic groups may result in overlooking a large proportion of at-risk individuals in some populations. [21][22][23] Measurement of specific body fat compartments requires costly medical equipment. Computed tomography or magnetic resonance imaging currently provides the most accurate measures for whole-body fat mass as well as tissue and organ adiposity.…”
Section: Defining Excess Body Weightmentioning
confidence: 99%
“…Pima Indians, who have among the highest reported prevalence levels of diabetes worldwide over the last 50 years, also have high levels of obesity and insulin resistance compared with other ethnic groups, which may be due to both innate susceptibility as well as lifestyle . In stark contrast, Asian Indians generally exhibit a thin body mass index (BMI) phenotype with high risk of diabetes, experiencing a high prevalence levels of type 2 diabetes and at lower BMI levels compared with other ethnic groups.…”
Section: Introductionmentioning
confidence: 99%